O combate ao trabalho escravo de imigrantes no Brasil: critérios hermenêuticos para efetiva proteção do trabalhador imigrante pelo ordenamento jurídico nacional - Bezerra, Laís Ribeiro de Sousa (2024)
This paper aims to analyze and propose hermeneutic criteria for the effective application of the international and national regulations that make up the Brazilian legal system for the repression and prevention of work in conditions analogous to slavery to the detriment of immigrants who enter the national territory. To this end, the issue is examined from the perspective of the grounds for decisions made by the National Judiciary and the public policies proposed and implemented by official bodies aimed at the formal and adequate inclusion of immigrants in the job market. Afterwards, the study proposes hermeneutic criteria to give effectiveness to the national legal order in confronting contemporary slavery to the detriment of immigrants in Brazilian territory. The dissertation study is arranged using a deductive approach, with qualitative bibliographic and documentary research relevant to migration and work in conditions similar to slavery. Scientific research is descriptive, according to the proposed purposes. The problem reveals its importance as it involves a topic of universal legal concern, which is reflected both in the broad growth of migratory flows in recent decades, for a variety of reasons, and in the observation that contemporary slavery continues to be present in the global context and has substantial relevance within of regulations aimed at protecting human rights. The work is divided into three parts. The first part is intended to examine the general aspects pertinent to the migration theme, including its interconnection with the exercise of work, official data on migratory flows present in Brazil and the analysis of the main national and international regulations protecting migrant workers. The second part deals with the panorama of combating slave labor at a national level, with a presentation of the main Brazilian statistical data, the interconnection between immigrant workers in Brazil and their susceptibility to social scourges such as contemporary slavery, followed by the analysis of the main norms aimed at combating of slave labor at global, interAmerican and national levels and, finally, the investigation of the material effectiveness, or not, of this normative body in relation to the proposed topic. The third and final part of the study is intended to propose hermeneutic criteria aimed at guaranteeing the material effectiveness of the normative systems analyzed in combating work in conditions analogous to slavery in the face of immigrants on Brazilian soil.